2015
DOI: 10.1016/j.toxrep.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental transfer of 2-naphthol in human placenta

Abstract: ObjectiveTo determine the transfer of 2-naphthol (2-NPH) in fullterm human placental tissues.MethodsSix placentas were studied. The ex-vivo dual closed-loop human placental cotyledon perfusion model was used. 2-NPH was added to the perfusate in the maternal compartment. Samples were obtained from the maternal and fetal up to 360 min measuring.ResultsThe mean fetal weight was 2880 ± 304.2 g. Mean perfused cotyledon weight was 26.3 (±5.5) g. All unperfused placental tissue samples contained NPH with a mean level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…39 The toxicity of 2-naphthol is much greater than that of 1-naphthol, which can damage the liver and kidneys of the human body and affect sperm activity. 40 In this study, we found that CehC1C2 can also hydroxylate 2-naphthol. To the best of our knowledge, the hydroxylase gene cehC1C2 cloned in this study is the first gene discovered and responsible for the 2-naphthol conversion.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…39 The toxicity of 2-naphthol is much greater than that of 1-naphthol, which can damage the liver and kidneys of the human body and affect sperm activity. 40 In this study, we found that CehC1C2 can also hydroxylate 2-naphthol. To the best of our knowledge, the hydroxylase gene cehC1C2 cloned in this study is the first gene discovered and responsible for the 2-naphthol conversion.…”
Section: Discussionmentioning
confidence: 58%
“…The naphthol residues in soil and water have seriously threatened food safety and human health . The toxicity of 2-naphthol is much greater than that of 1-naphthol, which can damage the liver and kidneys of the human body and affect sperm activity . In this study, we found that CehC1C2 can also hydroxylate 2-naphthol.…”
Section: Discussionmentioning
confidence: 65%
“…The developing fetus may be subject to adverse environments at home, in the workplace or through lifestyle activities (smoking, alcohol and drug intake, allergens, paint, pest/weed control, heavy metals, cleaning, body products such as perfumes and creams). Many of these substances can cross the placenta (Naphthalene a volatile polycyclic aromatic hydrocarbon related to solvent emissions is present in household products and pesticides – Mirghani et al, 2015 ; Nicotine – Wickström, 2007 ; Drugs and alcohol – Lange et al, 2014 ). There is evidence to suggest that the effects of some of these substances can also continue post-natally through breast milk fed to the new-born (heavy metals – Caserta et al, 2013 ; Dioxin – Rivezzi et al, 2013 ).…”
Section: Disentangling Genetic and Environmental Factorsmentioning
confidence: 99%
“…Subtle facial differences can be detected between populations reflecting the differing genetic structures in distinct population groups [20][21][22][23][24]. In addition, environmental factors can influence face shape over the course of life such as maternal smoking or alcohol [25][26][27], atmospheric toxins which can cross the placenta [28], childhood illnesses [29], and medical conditions [30,31]. 3D (computed tomography) images have also been explored in forensic facial reconstructions [32,33].…”
Section: Introductionmentioning
confidence: 99%